Conditions and Development of Agritourism Activities in Central and Eastern Europe – Example of Poland - Malgorzata ZDON-KORZENIOWSKA; Sławomir DOROCKI (Communications of International Proceedings, 2021)
The purpose of the article is to present the conditions and the state of development of agritourism activities in Central and Eastern Europe, with particular emphasis on the situation in Poland. Agritourism in Poland is an important form of business diversification, especially in rural and peripheral areas. The article indicates the basic determinants of agritourism development as well as the directions of development of agritourism offers in Poland on the basis of the analysis of the literature on the subject and statistical data, and a query of agritourism farms operating in Poland. The query concerned the offer profiles of agritourism farms and was carried out among those associated and recommended by the Polish Federation of Rural Tourism "Gospodarstwo Gościnne (eng. Guest House)" (PFTW GG). The research carried out for the purposes of this study indicates that agritourism companies in Poland are increasingly diversifying their offers adapting them to the requirements of tourists and the market situation. However, it seems that they do not fully recognize and take advantage of the benefits of belonging to e.g. associations or activities for the quality certification (e.g. categorization of facilities). In the conducted research, many theses have appeared that require verification based on in-depth qualitative research. The transformation of agritourism services in Poland can be an example of changes taking place in rural areas in Eastern Europe. The offer of agritourism farms often goes beyond the previous rustic scheme of agritourism offers.
Keywords: Agritourism; Europe; Poland; Tourism.